2009
DOI: 10.1590/s1516-80342009000400014
|View full text |Cite
|
Sign up to set email alerts
|

Incômodo causado pelo ruído a uma população de bombeiros

Abstract: OBJETIVO: Identificar o incômodo causado pelo ruído e queixas relacionadas à saúde auditiva em uma corporação de bombeiros do município Santo André (SP). MÉTODOS: Tratou-se de um estudo epidemiológico transversal de inquérito na população de 72 bombeiros do 8º Grupamento, 28 do setor administrativo, 20 do centro de ocorrência e 24 do atendimento operacional. Foi aplicado um protocolo composto por 57 questões referentes a dados pessoais, queixas auditivas, não auditivas e de incômodo. Também foi realizado o map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
3
7
0
3
Order By: Relevance
“…In the present study 7 individuals (23.3%) reported dizziness at some time in their lives, corroborating other authors who also found low dizziness indices in their samples 9,16 . A study involving 72 firefighters in order to identify discomfort caused by noise and complaints related to auditory health in this population revealed that only 9.7% complained of dizziness, 85.7% of whom described the frequency as "sometimes" and 14.3% as "always" 9 .…”
Section: Regulatory Guideline No 35 (Nr 35) Work Atsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study 7 individuals (23.3%) reported dizziness at some time in their lives, corroborating other authors who also found low dizziness indices in their samples 9,16 . A study involving 72 firefighters in order to identify discomfort caused by noise and complaints related to auditory health in this population revealed that only 9.7% complained of dizziness, 85.7% of whom described the frequency as "sometimes" and 14.3% as "always" 9 .…”
Section: Regulatory Guideline No 35 (Nr 35) Work Atsupporting
confidence: 92%
“…The literature contains a number of studies on firefighters involving pathologies such as cancer, cardiovascular and respiratory disorders, lesions, osteoarthritis in the hip and knee, mental disturbances, hearing loss, noise pollution, among others [7][8][9] . However, there were no studies that considered vestibular alterations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The discomfort that is felt in its presence can be described as indisposition, irritability and stress and is not directly related to the level of exposure. 22 Communication diffi culties have also been described, as well as headaches, sleep alterations, dizziness, hearing loss and tinnitus. 22 Individual and collective preventive measures regarding noise exposure are indicated.…”
Section: Introductionmentioning
confidence: 99%
“…22 Communication diffi culties have also been described, as well as headaches, sleep alterations, dizziness, hearing loss and tinnitus. 22 Individual and collective preventive measures regarding noise exposure are indicated. 14 A Brazilian study with approximately 2,000 teachers found that half of them had complaints about high or unbearable noise levels at school, inside or outside the classroom and associated with worse voice-related quality of life.…”
Section: Introductionmentioning
confidence: 99%